The Geography of Covid-19 Spread in Italy Using Social Media and Geospatial Data Analytics. Issue 3 (2nd September 2021) - Fernandez, Gabriela; Maione, Carol; Zaballa, Karenina; Bonnici, Norbert; Spitzberg, Brian H.; Carter, Jarai; Yang, Harrison; McKew, Jack; Bonora, Filippo; Ghodke, Shraddha S.; Jin, Chanwoo; De Ocampo, Rachelle; et al.
ABSTRACT: Since December 2019, Coronavirus has been spreading rapidly across the world. From its early stages, while the rest of the world was still new to COVID-19, Italy was one of the first and most severely hit countries. The chronic nature of the COVID-19 outbreak and untimely treatments were translated into an unstable social and emotional environment. This study explores the societal response to the first wave of the pandemic outbreak in Italy, looking at geographic variations, social and policy perspectives, and sentiments across northern, central, and southern regions. For this study, we collected nearly three million tweets associated with the coronavirus outbreak in the Italian regions of Lombardy, Lazio, and Sicily, during the months of March-May, 2020. A sentiment analysis was developed to (i) identify the spatio-temporal distribution of the polarity patterns of anger, fear, and joy; (ii) test correlation between these sentiments and COVID-19 cases; and (iii) determine the statistical significance between the sentiments across geographies. Findings provide insights on the relationship between sentiment variations and spatio-temporal case distribution associated with regional differences. These findings align with those of the "Track IT. COVID-19 International Survey, " that investigated the societal response of Italians to the new measures enforced by local governments. Overall, the findings of this study can be weaved together into important implications for emotional wellbeing and economic perspective.